Menyoal Kebebasan Beragama dan Penodaan Agama Di Indonesia - Yayan Sopyan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: Questioning the Religious Freedom and blasphemy in Indonesia. The presence of the Constitutional Court in the reform era is the strengthening of the foundations of constitutionalism in the Constitution of the Republic of Indonesia Year 1945. The Court in this case a role to enforce and the protector of the citizen's constitutional rights and the protector of the human rights. Including in this case, the right to religion and religious practices and teachings of their respective religions, in accordance with the constitutional mandate. However, on the other hand there is the discourse of freedom of expression and freedom of speech includes freedom to broadcast religious beliefs and understanding of the